2016
DOI: 10.5530/ijopp.9.1.5
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Assessment of Patients Health Related Quality of Life During Tuberculosis Treatment in a Tertiary Care Teaching Hospital

Abstract: Background: Tuberculosis is one of the leading causes of mortality and morbidity around the world, infecting approximately 8 billion people, with an annual death rate of close to 1 million. The present study was conducted to evaluate the impact of tuberculosis treatment on health related quality of life (HRQoL) of patients with active and inactive tuberculosis by evolving HRQoL questionnaire (SF-36v2). Methodology: A prospective follow-up study was conducted for total 70 patients (56 men and 14 women) diagnose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
1
4
0
1
Order By: Relevance
“…It was evident from this study that TB affects the dimensions of mobility, self-care, usual activities, pain/discomfort and anxiety/depression of HRQOL in keeping with results of other studies in different countries that assessed HRQOL of TB patients using different instruments [14][15][16][17]33]. It was also evident that HRQOL of TB patients has been improved significantly with standard anti-TB medication for 6 months which is also consistent with similar studies done in North India among new PTB patients using WHOQOL-BREF [8], another study done in India among PTB patients using SF-36 [21], in Indonesia among smear-positive PTB patients using SGRQ [22] and in Pakistan among new PTB patients using EQ-5D-3L [17]. The only study reported from Sri Lanka [16] also shows similar results of significant improvement of the HRQOL (p < 0.001) among TB patients during the medication period, as measured by the WHOQOL-BREF.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was evident from this study that TB affects the dimensions of mobility, self-care, usual activities, pain/discomfort and anxiety/depression of HRQOL in keeping with results of other studies in different countries that assessed HRQOL of TB patients using different instruments [14][15][16][17]33]. It was also evident that HRQOL of TB patients has been improved significantly with standard anti-TB medication for 6 months which is also consistent with similar studies done in North India among new PTB patients using WHOQOL-BREF [8], another study done in India among PTB patients using SF-36 [21], in Indonesia among smear-positive PTB patients using SGRQ [22] and in Pakistan among new PTB patients using EQ-5D-3L [17]. The only study reported from Sri Lanka [16] also shows similar results of significant improvement of the HRQOL (p < 0.001) among TB patients during the medication period, as measured by the WHOQOL-BREF.…”
Section: Discussionsupporting
confidence: 88%
“…Results show that HRQOL was very low at the initiation of treatment and improved significantly at the completion of treatment [15,20]. Different tools such as World Health Organization Quality of Life BREF (WHOQOL-BREF) [8], Short-Form 36 (SF-36) [21] and St. George's Respiratory Questionnaire (SGRQ) [22] have been used to measure HRQOL. The authors have concluded that HRQOL indicators are important as patient-reported health outcomes of TB patients with other clinical and laboratory indicators to assess the complete health status of patients [8,21,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remaining cases were either with one (or) more co-morbid conditions. Institutional patient's mortality and morbidity due to certain endemicity among the inpatient population is currently essential to reduce the impact of clinical consequences 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, just the diagnosis of TB alone may lead to depression and anxiety or contribute to the worsening and persistence of disease symptoms, which follows with fear, frustration, and disappointment 9 . Furthermore, most TB patients have no knowledge of disease progress and treatment which can cause more anxiety and feelings of frustration and decreases the QOL among the patients 10 .…”
Section: Introductionmentioning
confidence: 99%